Relational geographies of cyberterrorism and cyberwar. Issue 2 (3rd May 2016) - Warf, Barney; Fekete, Emily
Abstract : Cyberterrorism is an increasingly pervasive term in the mainstream media; however, its definition remains vague at best. As the use of information technology continues to expand, the real and virtual worlds are evermore entwined, including the use of such technology for military purposes. Contemporary work in border studies explains the growing permeability of state borders. Inspired by the works of Paul Virilio, this paper holds that cyberattacks exemplify the increasingly relational quality of war. Case studies of China, Iran, North Korea, Syria and Russia are offered to illustrate this trend.